(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
In this article, the factors of the origin of the concept of meritocracy, which is gaining relevance today, in Ancient China and its importance, the stages of development of the meritocracy system in China today, the possibility of coexistence of democracy and meritocracy in Chinese politics is also expressed in the economic sphere, meritocratic principles in achieving efficiency in public administration. the importance of implementation is discussed.